Earthquake Propensity and the Politics of Mortality Prevention - Plumper, Thomas (The World Bank, 2010)
Governments can significantly reduce earthquake mortality by implementing and enforcing quake-proof construction regulation. The authors examine why many governments do not. Contrary to intuition, controlling for the strength and location of actual earthquakes, mortality is lower in countries with higher earthquake propensity, where the payoffs to mortality prevention are higher. Importantly, however, the government response to earthquake propensity depends on country income and the political incentives of governments to provide public goods to citizens. The opportunity costs of earthquake mortality prevention are higher in poorer countries; rich countries invest more in mortality prevention than poor countries in response to a higher earthquake propensity. Similarly, governments that have fewer incentives to provide public goods, such as younger democracies, autocracies with less institutionalized ruling parties and countries with corrupt regimes, respond less to an elevated quake propensity. They therefore have higher mortality at any level of quake propensity compared to older democracies, autocracies with highly institutionalized parties and non-corrupt regimes, respectively. The authors find robust evidence for these predictions in our analysis of earthquake mortality over the period 1960 to 2005